2022
DOI: 10.1007/s40620-022-01259-3
|View full text |Cite
|
Sign up to set email alerts
|

Methods for the dietary assessment of adult kidney stone formers: a scoping review

Abstract: Background Kidney stones are a frequent and potentially severe condition, affecting 5–10% of the European population. Causes are multifactorial, diet in particular plays a major role in the formation and management of kidney stones. The aim of this scoping review is to assess the methods used to study the diet of adult kidney stone formers. Methods We conducted a systematic search in Medline Ovid SP, Embase, Cinahl, Cochrane (CENTRAL), Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This study was also indicated that laparoscopic surgery was better than traditional surgery in these three aspects. The reason may be that long-term surgical posture has an adverse effect on the comfort of patients, which may affect the late recovery of patients [ 27 ]. In addition, laparoscopic surgery has fewer complications than traditional surgery, which is also one of the reasons for the high life quality of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was also indicated that laparoscopic surgery was better than traditional surgery in these three aspects. The reason may be that long-term surgical posture has an adverse effect on the comfort of patients, which may affect the late recovery of patients [ 27 ]. In addition, laparoscopic surgery has fewer complications than traditional surgery, which is also one of the reasons for the high life quality of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of diet for kidney stone disease has been known for a long time and been confirmed in various cohorts such as NHANES and others [19,[29][30][31][32]. However, in these cohorts, information on diet is mostly derived from FFQ or other forms of retrospective interviews [33]. Most food questionnaires assess dietary intake only for groups of nutrients (i.e., proteins, fat, carbohydrates) or the frequency or size of meals.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported methods based on recall, such as food frequency questionnaires or 24-h dietary recalls, or based on real-time recordings, e.g. food diaries, in combination with objective nutritional biomarkers, are useful options for assessing the dietary habits of kidney stone patients [ 28 ]. In addition to the type and quantity of food consumed, the timing of meals and the type and volume of beverages consumed should also be recorded.…”
Section: Classification and Diagnostic Measuresmentioning
confidence: 99%